Acute Hypoglycemic and Antidiabetic Effect of Teuhetenone A Isolated from Turnera diffusa - Parra Naranjo, Aída Salomé; Delgado Montemayor, Cecilia; Fraga López, Alejandra; Castañeda Corral, Gabriela; Salazar Aranda, Ricardo; Acevedo Fernández, Juan José; Waksman Minsky, Noemí Herminia (2017)
Abstract: Diabetes mellitus is a chronic degenerative disease that causes long-term complications and represents a serious public health problem. Turnera diffusa (damiana) is a shrub that grows throughout Mexico and is traditionally used for many illnesses including diabetes. Although a large number of plant metabolites are known, there are no reports indicating which of these are responsible for this activity, and this identiﬁcation was the objective of the present work. Through bioassay-guided fractionation of a methanolic extract obtained from the aerial part of T. diffusa, teuhetenone A was isolated and identiﬁed as the main metabolite responsible for the plant’s hypoglycemic activity. Alpha-glucosidase inhibitory activity and cytotoxicity of this metabolite were determined. Hypoglycemic and antidiabetic activities were evaluated in a murine model of diabetes in vivo, by monitoring glucose levels for six hours and comparing them with levels after administering various controls. Teuhetenone A was not cytotoxic at the tested concentrations, and did not show inhibitory activity in the glucosidase test, and the in vivo assays showed a gradual reductioninglucoselevelsinnormoglycemicanddiabeticmice. Consideringtheseresults,wesuggest that teuhetenone A has potential as an antidiabetic compound, which could be further submitted to preclinical assays. Keywords: diabetes mellitus; damiana; teuhetenone A; antidiabetic; Turnera diffusa